Enhancing student assessment in online learning: a contemporary appraisal / Abd Rasyid Ramli, Burhanuddin Wahab and Ahmad Fauzi Yahaya - Ramli, Abd Rasyid; Wahab, Burhanuddin; Yahaya, Ahmad Fauzi (Universiti Teknologi MARA, Kedah, 2024)
The landscape of education has undergone a seismic shift with the widespread adoption of online learning. In recent years, student assessment in this digital realm has become a focal point, presenting both opportunities and challenges. The COVID-19 pandemic further accelerated the reliance on online education, magnifying the significance of effective assessment strategies in virtual classrooms. This paper navigates through the current situation of student assessment in online learning by incorporating the latest research findings and building upon prior studies to provide a nuanced understanding. The current situation of student assessment in online learning is marked by a dual reality. On one hand, the flexibility and accessibility offered by digital platforms have opened new avenues for assessment methodologies. On the other hand, challenges such as ensuring academic integrity, addressing technological disparities, and maintaining engagement persist.